PEMANFAATAN ARANG AKTIF KULIT PISANG KEPOK (MUSA NORMALIS) SEBAGAI ADSORBEN UNTUK MENURUNKAN ANGKA PEROKSIDA DAN ASAM LEMAK BEBAS MINYAK GORENG BEKAS - Nasir, Neni Sri Wahyuni; Nurhaeni, Nurhaeni; Musafira, Musafira (Univ. Tadulako, 2014)
This research was about the useofactive charcoal of the banana peel (Musa normalis) as adsorbent to degrade peroxide and free faty acid of the used cooking oil. The aims of thisresearch was to determine the best rasio of active charcoal of the banana peel as adsorbent, and the best concentration of NaOH as activator to reduceperoxideand free faty acid of the used cooking oil. This research used 5 level oftreatmentswhich based on CRD, the ratio variation were 2.5, 5.0, 7.5, 10.0 and 12.5 % and the concentrations of NaOH variation were 0.125, 0.25, 0.5, 1 and 2 N. The result showed that the best ratio was occurred in the 10.0 % and the concentration of 1 N NaOH. This value indicated that the banana peel was an adsorben, which can be used inincrease quality of the used cooking oil.